Subacute sarin exposure disrupted the homeostasis of purine and pyrimidine metabolism in guinea pig striatum studied by integrated metabolomic, lipidomic and proteomic analysis. (15th August 2022) - Shi, Meng; Zhang, Ruihua; Jin, Qian; Cui, Yalan; Shi, Jingjing; Chen, Xuejun; Shi, Tong; Zhang, Yi; Zhu, Siqing; Zong, Xingxing; Xu, Jianfu; Wang, Chen; et al.
Abstract: Sarin was used as a chemical weapon due to its high neurotoxicity and mortality. Subacute sarin induced cognitive and behavioral disorder. However, the underlying mechanism is still unclear. Here we offered a multi-omic approach for the analysis of altered metabolites, lipids, and proteins to explore the neurotoxicity of subacute sarin. Guinea pigs were administered between the shoulder blades 16.8 μg/kg of sarin in a volume of 1.0 ml/kg body weight by subcutaneous injection once daily for 14 days. At the end of the final injection, guinea pigs were sacrificed, and striatum were dissected for analysis. A total of 138 different metabolites were identified in the metabolome analysis. Lipids and lipid-like molecules is the largest group (38.41%). For lipidomic analysis, a total of 216 lipids were identified. In proteomic study, over 4300 proteins were identified and quantified. By integrating these enriched components, we demonstrated that the joint pathways disturbed by subacute sarin mainly involving lipid, purine and pyrimidine metabolism in guinea pig striatum. Overall, this study highlights the powerfulness of omics platforms to deepen the understanding of nerve agents caused neurotoxicity. Graphical Abstract: ga1 Highlights: Subacute sarin disturbed the cognitive and motor abilities in guinea pigs. Subacute sarin disturbed purine and pyrimidine metabolism in striatum. Nucleotides play important roles in alleviating neurotoxicity of nerve agents. Omics platforms are useful to deepen the understanding of nerve agents caused neurotoxicity.